If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 1 = -16 Reorder the terms: 1 + 5x = -16 Solving 1 + 5x = -16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 5x = -16 + -1 Combine like terms: 1 + -1 = 0 0 + 5x = -16 + -1 5x = -16 + -1 Combine like terms: -16 + -1 = -17 5x = -17 Divide each side by '5'. x = -3.4 Simplifying x = -3.4
| 6(y+2)=-3(6y-1)+6y | | 13X=10X-9 | | Y=-x(x-2) | | 3(1)+2(6)=9 | | 3x^2+5x-2y^2=0 | | -x(0)+5y=15 | | -x+0=15 | | 2y-42=4 | | a+4-a(a+4)=0 | | 5h+24=-8(b-6)+6b | | sin(x)=0.5625 | | 1a-4b+2c=0 | | 8p=9 | | 2+19=43 | | sinx=0.5625 | | x(x-8)+2(x-8)=0 | | 5+3y=9 | | Y=5x^2+35 | | z-34.7=68.2 | | 10x+8y+z=100 | | 6x-30=6x+12 | | 5ln(x^2)=4ln(x^3)+6 | | 3x^2-11=37 | | Cry+z=9fory | | y(y-12)+y-12=0 | | 12X+2=76 | | 12X+2=78 | | -4(2x-6)=-6 | | r/5+5=8 | | c/3+3=7 | | -2x+9+4x=-2 | | p/5+7=16 |